AWARE Platform: early warning and action platform for flood resilience in Nigeria - Oke, Adebayo; Amarnath, Giriraj; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
As the climate heats up, the water cycle is twisting and contorting, unleashing a torrent of disruptions. More frequent, ferocious floods and droughts, unpredictable downpours, and gnawing erosion are just the tip of the iceberg. Poor water quality, disease outbreaks, and a host of uncertainties are all conspiring to rip apart the delicate web of life that sustains us. Nigeria is recognized as vulnerable to climate change impacts and ranked 160 out of 181 countries due to a combination of political, geographic, and social factors in the 2020 ND-GAIN Indexii . The ND-GAIN ranks 181 countries using a score which calculates a country’s vulnerability to climate change and other global challenges as well as their readiness to improve resilience. The socio-economic impact of floods in Nigeria has been colossal. In 2012 more than 2.3 million people were displaced, 363 lost their lives and 16 million people were impacted in various waysiii . The economic value of the loss was over US$16.9 billioniv . Again ten years later in 2022, another major flood led to the loss of 600 lives. Also, 3.2 million people were affected across 34 of the 36 states of the federation and the Federal Capital Territory. The Nigeria Bureau of Statistics in 2023v reported the devastating impact of the 2022 flood to be in the range of US$3.79 billion to $9.12 billion, with the best (median) estimate at $6.68 billion. The economic value of the agricultural-related losses due to the 2022 floods was about N700 billion. Agricultural lands, crops, infrastructure, and rural livelihood continue to be destroyed almost annually. Past efforts to mitigate flood risks in Nigeria from prevention to preparedness, have often been hampered by poor coordination, inadequate resources, and lack of cutting-edge tools, limited platform to integrate relevant data where such needed data are available. As climate change intensifies, the expected increase in extreme weather events leaves the country vulnerable. Now, a critical examination of all relevant disaster management organizations, technical institutions, humanitarian organizations, and civil societies needs to have robust coordination in promoting holistic and systemic flood risk management is crucial. Nigeria’s government and institutions must identify gaps and deploy more concrete, workable approaches to shield vulnerable Nigerians and their livelihoods from the devastating impacts of future floods.